Saving, Investment, and Current Account Surplus in Developing Asia - Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2009)
An integral part of global current account imbalances is the large and persistent current account surplus developing Asia has run since the 1997–1998 Asian crisis. A country's current account surplus is, by definition, equal to its net saving. The central objective of this paper is to investigate the extent to which the saving and investment rate of Asian countries can be explained by the underlying fundamental determinants of saving and investment such as gross domestic product growth and demographic factors. Our empirical analysis yields two key findings. First, we find stronger evidence of oversaving than underinvestment in the region. Second, we find stronger evidence of overinvestment prior to the Asian crisis than underinvestment after the Asian crisis. This suggests that the key to rebalancing Asian growth toward domestic sources lies in promoting consumption rather than investment.
hdl:11540/1803
Keywords: E21; E22; F32; 330; Saving; investment; current account balance; global imbalance; Asia; Sparen; Auslandsinvestition; Außenwirtschaftliches Gleichgewicht; Leistungsbilanz; Wirtschaftswachstum; Asien